If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + 7r) + -6 = 379 (1 * -7 + 7r * -7) + -6 = 379 (-7 + -49r) + -6 = 379 Reorder the terms: -7 + -6 + -49r = 379 Combine like terms: -7 + -6 = -13 -13 + -49r = 379 Solving -13 + -49r = 379 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -49r = 379 + 13 Combine like terms: -13 + 13 = 0 0 + -49r = 379 + 13 -49r = 379 + 13 Combine like terms: 379 + 13 = 392 -49r = 392 Divide each side by '-49'. r = -8 Simplifying r = -8
| s^2+8s-9=0 | | 125m-75m+43875=46125-175m | | 2x+3(-8)=0 | | 15x-2.4x=0.6+7.6x | | -4(x)-2y=-12 | | 25p^2-4=0 | | 5x=40*0.5 | | a=h(b+c)solve(b) | | 2x+5(x-1)= | | 3(-11)[5(-3)-7(-2)]= | | 6xrqw+13xrqw=133 | | 9s-36=5s | | 64g^3-125h^3=0 | | 13(x-4)=8x-32 | | 16t^2=-h+100 | | 3/4+1/4x=3/4x-1/4 | | -4=3n-7n | | 2x-60=x | | x-2=14*2 | | 16t^2+h=100 | | 1-11-3x=32 | | x+by=c*x | | (2m-7)squared= | | 2(7)-2x=6 | | 12x-4(3x)=0 | | 4b-8b^2=0 | | x/2-1/5=x/3+1/4 | | Y+5/8=-2 | | -17x=391 | | 7y-18=-46+3y | | 6(1)-10x=77 | | 2x-5(x-2)=-6+3x-20 |